Microwave Planar Sensor for Determination of the Permittivity of Dielectric Material - Mohd Khairy Ismail; Zahriladha Zakaria; Nornikman Hassan; Sam Weng Yik; Mohd Mawardy Abdullah (Bulletin of Electrical Engineering and Informatics, 2018)
This paper proposed a single port rectangular microwave resonator sensor. This sensor operates at the resonance frequency of 4GHz. The sensor consists of micro-strip transmission line and applied the enhancement method. The enhancement method is able to improve the return loss of the sensor, respectively. Plus, the proposed sensor is designed and fabricated on Roger 5880 substrate. Based on the results, the percentage of error for the proposed rectangular sensor is 0.2% to 8%. The Q-factor of the sensor is 174.